Trajectories of night light exposure and risk of overweight and obesity: a 15-year longitudinal cohort study of 218,239 Chinese children - Xijie Wang; Manman Chen; Din Son Tan; Jie Hu; Bin Dong; Yu Jiang; Wannian Liang (BMC Medicine)
Abstract Background Light at night (LAN) is found to be associated with elevated overweight and obesity in broad population. However, evidence for the long-term LAN exposure trajectories and its influence to weight gain remained limited, especially to school-aged children who experience critical physical development. We aimed to analyze variations in body weight among children with different LAN exposure profiles, and how varying levels of LAN exposure influenced children’s overweight (including obesity) risk overt time. Methods Children who had ≥ 5 school health examinations between 2005 and 2020 in Zhongshan were recruited in this population-based longitudinal study. LAN data of each child at each survey year were modeled with group-based trajectory model and named as sharp rise (reference; 5.5%), mild rise, high stable (69.7%), and decline. Differences of overweight incidence between groups were analyzed. Results Among 218,283 children (1,318,542 measurements; 53.1% boys; baseline mean [SE] age, 9.1 [2.5]), 12,050 (5.5%) were categorized in the sharp rise group and 152,030 (69.7%) in the stable high group. In the 189,011 participants categorized as normal or underweight at baseline, the overall incidence of overweight during follow-up was 8.80/1000 person-years (95% CI: 8.69, 8.91). Compared to the sharp rise group, the hazard ratios (HR) for developing overweight were 1.67 (95% CI: 1.28, 2.18) for boys and 1.56 (95% CI: 1.21, 2.01) for girls in stable high group, followed by the mild rise group. The HRs in decline group were non-significant. Overall, the stable high trajectory of LAN exposure accounted for 40.24% (range: 22.14, 54.14) of overweight risk in boys and 36.09% (range: 17.79, 50.31) in girls, while the mild rise group contributed approximately 23% to the overall risk. Conclusions Higher LAN exposure trajectories, especially at early school age, had persistent effect to overweight and obesity risk in school-aged children. Interventions to reduce LAN exposure during school age may help reduce excessive weight gain in children.